"Diffusion with modifications": Nubian assemblages in the central Negev highlands of Israel and their implications for Middle Paleolithic inter-regional interactions. (15th July 2016) - Goder-Goldberger, Mae; Gubenko, Natalia; Hovers, Erella
Abstract: Nubian Levallois cores, now known from sites in eastern Africa, the Nile Valley and Arabia, have been used as a material culture marker for Upper Pleistocene dispersals of hominins out of Africa. The Levantine corridor, being the only land route connecting Africa to Eurasia, has been viewed as a possible dispersal route. We report here on lithic assemblages from the Negev highlands of Israel that contain both Levallois centripetal and Nubian-type cores. Wetter conditions over the Sahara and Negev deserts during MIS 6a–5e provided a generally continuous environmental corridor into the Levant that enabled the dispersal of hominin groups bearing the Nubian variant of prepared core technologies. The Negev assemblages draw renewed attention to the place of the Levant as one of the dispersal routes out of Africa during the Late Pleistocene and could suggest that processes of human dispersals and cultural diffusion resulted in the spread of Nubian technology across eastern Africa, the western Sahara and the Nile Valley, the southern Levant and Arabia.